Urinary excretion profile of prednisolone and prednisone after rectal administration: Significance in antidoping analysis. Issue 11 (12th August 2022) - Iannella, Loredana; Comunità, Fabio; Botrè, Francesco; Colamonici, Cristiana; Curcio, Davide; de la Torre, Xavier; Mazzarino, Monica
Abstract: The rectal administration of glucocorticoids, as well as any injectable, and oral ones, is currently prohibited by the World Anti‐Doping Agency when occurs "in competition." A reporting level of 100 ng/ml for prednisolone and 300 ng/ml for prednisone was established to discriminate the allowed and the prohibited administration. Here, the urinary excretion profiles of prednisone and prednisolone were evaluated in five volunteers in therapy with glucocorticoid‐based rectal formulations containing prednisone or prednisolone caproate. The urinary levels of the excreted target compounds were determined by liquid chromatography–tandem mass spectrometry (LC‐MS/MS) following the procedure validated and currently in use in our laboratory to detect and quantitate glucocorticoids in urine. Predictably, the excretion trend of the analytes of interest were generally comparable with those obtained after oral administration, even if the excretion profile showed a broad interindividual variability, with the absorption rate and the systemic bioavailability after rectal administration being strongly influenced by the type of formulations (suppository or rectal cream, in our case) as well as the physiological conditions of the absorption area. Results showed that the target compounds were detectable for at least 30 h after drug administration. After suppository administration, prednisolone levels reached the maximum after 3 h from drug administration and then dropped below the reporting level after 15–21 h; prednisone reached the maximum after 3 h from drug administration, and then dropped below the reporting level after 12–15 h. After cream administration, both prednisone and prednisolone levels remained in a concentration below the reporting level throughout the entire monitored period. Abstract : In this work, excretion profile of prednisone and prednisolone was evaluated in subjects in therapy with glucocorticoids‐based rectal formulations. The absorption rate and the systemic bioavailability of an active principle after rectal administration are strongly influenced by the type of formulations and the physiological conditions of the absorption area. The urinary levels of the target analytes after ointment application were significantly lower than those measured after suppository administration and similar to those reported in previous articles after local administration.